Cytosine Radical Cations: A Gas‐Phase Study Combining IRMPD Spectroscopy, UVPD Spectroscopy, Ion–Molecule Reactions, and Theoretical Calculations. Issue 10 (7th April 2017) - Lesslie, Michael; Lawler, John T.; Dang, Andy; Korn, Joseph A.; Bím, Daniel; Steinmetz, Vincent; Maître, Philippe; Tureček, Frantisek; Ryzhov, Victor
Abstract: The radical cation of cytosine (Cyt .+ ) is generated by dissociative oxidation from a ternary Cu II complex in the gas phase. The radical cation is characterized by infrared multiple photon dissociation (IRMPD) spectroscopy in the fingerprint region, UV/Vis photodissociation (UVPD) spectroscopy, ion–molecule reactions, and theoretical calculations (density functional theory and ab initio). The experimental IRMPD spectrum features diagnostic bands for two enol‐amino and two keto‐amino tautomers of Cyt .+ that are calculated to be among the lowest energy isomers, in agreement with a previous study. Although the UVPD action spectrum can also be matched to a combination of the four lowest energy tautomers, the presence of a nonclassical distonic radical cation cannot be ruled out. Its formation is, however, unlikely due to the high energy of this isomer and the respective ternary Cu II complex. Gas‐phase ion–molecule reactions showed that Cyt .+ undergoes hydrogen‐atom abstraction from 1‐propanethiol, radical recombination reactions with nitric oxide, and electron transfer from dimethyl disulfide. Abstract : All mixed up : The cytosine radical cation (Cyt .+ ), formed by dissociation from a ternary Cu II complex, is present as a mixture of several low‐energy amino‐type tautomers in the gas phase. In this study, specific isomers are distinguished by the use of IR and UV action spectroscopy techniques, ion–molecule reactions, and theoretical calculations.